Towards a Theoretical Framework for Understanding Capitalist Violence against Child Labor - Raju Das; Ashley Chen (World Review of Political Economy, 2019)
More than 150–200 million children work for a living in the world. A large number of them experience violence. The economic aspect of child labor has received much attention (as has the topic of violence against children as children), and rightly so. But the extra-economic aspect of child labor (i.e., the sheer violence against children as workers in the market-place and the workplace) has been relatively neglected. It is necessary to conduct empirical studies on the topic, which, however, require prior theoretical work. The aim of this paper is to provide a theoretical framework on violence against child labor. Central to this framework are three inter-connected arguments: the fact that under certain circumstances, and contrary to a widely-prevalent standpoint, capitalism produces, and makes use of, a pool of workers who lack the freedom to enter and exit a labor contract; the universal logic of capitalist accumulation interacting with the context where some workers are children; and finally, the fact that violence against child labor is enabled by a specific cultural aspect of capitalist society, “childism.”